Comparative Evaluation of Scalpel, Electrosurgery, and Laser in Periodontal Surgery: A Systematic Case Review - Mappangara, Surijana; Hatta, Ridhayani; Atlanta, Maya Masyita (Indonesian Dental Association, 2024)
In periodontal surgery, utilizing a conservative approach yields more aesthetically pleasing outcomes while reducing patient morbidity and tissue damage. The development of tools such as electrosurgery and lasers for periodontal treatment has facilitated the implementation of these conservative procedures. This study aims to evaluate the efficacy, outcomes, and postoperative complications of scalpel, electrosurgery, and laser techniques in the periodontal surgery. This article was created by making a research question using the PICO method and searching for articles from PubMed/MEDLINE, Web of Science, Scopus, ScienceDirect, and Google Scholar from 2019-2023. This study used the PRISMA standard guidelines. Almost all studies in this systematic case review compared the three therapies in treating gingival hyperpigmentation. Only one study discussed the treatment of gingival enlargement using the gingivectomy method. Laser use in periodontal surgery is best compared to electrosurgery or scalpel in effectiveness, quality, outcome, postoperative complications, and wound healing. Dry and bloodless surgical wounds, instant sterilization of the surgical area, reduced bacteremia, mechanical trauma, minimal postoperative swelling and scarring, and minimal postoperative pain point to the effectiveness of using lasers compared to surgery with electrosurgery or scalpel techniques. Laser therapy in periodontal surgery is superior to scalpel and electrosurgery, offering faster treatment, fewer postoperative complications, enhanced wound healing, and higher patient satisfaction. These findings support the adoption of laser techniques for optimal clinical and patient outcomes.